Estudos eletroquímicos de interação do nitroderivado 2-[(4-nitrofenil)-amino]-4,5,6,7-tetraidro-4h-benzo[β]tiofeno-3-carbonitrila com β-ciclodextrina e PAMAM 3ª geração - Silva, Marilya Palmeira Galdino da (2017)
Nitroaromatic compounds are very used in the pharmaceutical industry for their known biological properties. One of the probable mechanisms of action of this class of compounds may be involved in redox reactions. The identification of nitro and its products, for a technique simple, sensitive and low cost technique such as electrochemical techniques, is fundamental, because through them it is possible to analyze the solubilization process of these compounds in association with some encapsulating agents. A feature of nitro compound studied, 2 - [(4-nitrophenyl) amino]-4,5,6,7-tetrahydro-4H-benzo [β] thiophene-3-carbonitrile, (6CN10) is its low solubility in water, which justifies its combination with substances such as cyclodextrin and dendrimers, such as PAMAM. The formation of an inclusion complex between 6CN10 and β-cyclodextrin and 6CN10 and PAMAM 3rd generation was evaluated in this work through electrochemical and spectroscopic techniques. The electrochemical system was composed of three electrodes, Ag/AgCl/Cl- saturated (reference), platinum (auxiliary), glassy carbon with and without modification with carbon nanotubes (NTC) or gold (Au) (working) in a buffered medium pH 7.03 with and without a cosolvent and a Na2SO4 solution of 0.2 mol L-1. Also was performed spectroscopic studies by UVVis in aqueous-ethanolic medium in different concentrations of β-Cyclodextrin, as well as the characterization of the complex 6CN10: PAMAM in methanolic solution. The studies demonstrated that the 6CN10 has standard reduction mechanism of nitroaromatic in potential within the expected range for compounds with biological activity its mechanism of action may be associated with the redox process The first analysis showed the interaction of 6CN10 as β-CD and the influence of time in this process. By forming a self-assembled monolayer (SAM) of β-CD-SH on the Au electrode it was possible to determine the equilibrium constant between the complex 6CN10:β-CD with value 3,3x105 M-1. Already by spectrophotometric methods, the constant was 7,86x104 M-1. Regarding the PAMAM the first results verified the influence of time on complex formation between 6CN10:PAMAM, reaching the optimum time of 30 minutes. Then With the increasing variations in the concentration of 6CN10 it was possible to determine the equilibrium constant (KF = 5,61x105 M-1) between the complex 6CN10:PAMAM, in NTC sensor. It is observed that the obtained value is relatively higher in comparison with the electrochemical constant for the complex 6CN10:β-CD. This favoring behavior 6CN10:PAMAM complex can also be observed by the values of LD and LQ obtained, which were, respectively, 1,49x10-6 and 4,96x10-6 mol L-1 to the complex with PAMAM and 1,83x10-6 and 6,1x10-6 mol L-1 to β-CD. When the SAM of PAMAM-MUA was used the constant obtained was of 2,16x105 M-1. In characterizing the 6CN10:PAMAM complex per UV-Vis, the results show that a higher amount than the number of PAMAM ramifications (32 ramifications) and of the 6CN10 interacted, suggesting that the nitro interacted of different forms with PAMAM. Both encapsulating agents demonstrated efficiency for complex formation with the compound under study, but PAMAM presented subtle advantage. However both could be used for the development of different pharmaceutical formulations containing the nitro compound.